Sistem Kerja dan Peran PPK Panyabungan Selatan dalam Penyelenggaraan Pilkada Serentak Tahun 2024 di Kabupaten Mandailing Natal - Azizah, Fitri; Harahap, Aprilinda M.; Adnir, Farid (Multiverse: Open Multidisciplinary Journal, 2024)
This study examines the working system and the role of the Subdistrict Election Committee (PPK) of South Panyabungan in supporting the success of the 2024 simultaneous regional elections (Pilkada) in Mandailing Natal Regency, Indonesia. The research is motivated by the strategic role of PPK as a frontline executor in the electoral process at the subdistrict level, which significantly influences electoral integrity and voter participation. The central research question explores how the PPK's organizational structure, task implementation, and coordination mechanisms contribute to the smooth execution of Pilkada. Employing a qualitative descriptive method, data were collected through in-depth interviews with election officials, field observations, and document analysis. The findings reveal that the PPK of South Panyabungan plays a pivotal role in administrative preparation, community engagement, and inter-institutional coordination. However, challenges such as limited resources, time constraints, and varying levels of voter education remain. The study concludes that despite these constraints, the PPK demonstrated adaptive strategies and institutional resilience, which collectively contributed to the effective implementation of the 2024 regional elections at the grassroots level.